2009
DOI: 10.1080/08854726.2010.480829
|View full text |Cite
|
Sign up to set email alerts
|

Are Surveys on Quality Improvement of Healthcare Chaplaincy Emotionally Distressing for Patients? A Pilot Study

Abstract: In recent years, much research work has been done in the field of religion/spirituality and healthcare. Many chaplains are wary of doing research because they assume it is cumbersome or potentially deleterious to ill patients. The aim of the present pilot study is, therefore, to find out if research on quality improvement of healthcare chaplaincy is emotionally distressing for patients. In connection with a questionnaire about quality improvement proceeding of healthcare chaplaincy, patients were asked subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Social and religious data were collected through a 7-item-questionnaire. It has been demonstrated that assessing spirituality in this way doesn't distress the patients (Winter-Pfandler & Morgenthaler, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Social and religious data were collected through a 7-item-questionnaire. It has been demonstrated that assessing spirituality in this way doesn't distress the patients (Winter-Pfandler & Morgenthaler, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…There are sufficient studies to show that each survey has limitations. [176][177][178][179][180][181][182][183][184][185][186][187][188][189][190][191] Potential users are often aware of these limitations already. A study by Macmillan Cancer Support 13 showed that commissioners valued CPES free-text data, especially as a means of capturing broad information from patients and opening up conversations about patient experience between commissioners and providers.…”
Section: Appendix 6 Concept-mapping Workhop Participantsmentioning
confidence: 99%